Zinc oxide nano array with adjustable size as well as preparation method and application of zinc oxide nano array
By using photolithography templates to prepare zinc oxide nanorod array cluster structures during hydrothermal growth, the problem of low energy conversion efficiency of zinc oxide nanomaterials in the field of photo-electric conversion is solved, and efficient photoelectric conversion and mechanical stability are achieved , suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411415952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-27
AI Technical Summary
Existing zinc oxide (ZnO) nanomaterials have low energy conversion efficiency in the field of photo-electric conversion, especially in photovoltaic and photoconductive photodetectors, and photoelectric conversion of solar cells prepared using 20μm ZnO nanowires. The efficiency is only 1.5%, and the surface area of ZnO nanostructures needs to be improved to improve conversion efficiency.
By using photolithographic templates to prepare an adjustable-size zinc oxide nanorod array cluster structure during hydrothermal growth, the upright growth and uniform arrangement of zinc oxide nanorods are achieved, and their surface area and mechanical stability are enhanced, making it suitable for large-scale production and industrialization application.
Accurate positioning and control of ZnO nanorod array clusters is achieved, the photoelectric conversion efficiency is improved, the preparation process is simplified, the cost is reduced, and it is suitable for photodetectors, photocatalysts and solar cells.
Smart Images

Figure CN119208022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a size-adjustable zinc oxide nanoarray and a preparation method and application thereof. Background Art
[0002] The development of energy materials has become one of the hot topics in the field of materials science and engineering, and has attracted widespread attention due to its unique advantages in energy storage and conversion. Among them, nanomaterials have special physical and chemical properties and have been studied in depth in many fields. In recent years, research has been devoted to exploring the novel structures and mechanisms of various nanomaterials in energy applications, hoping to achieve more efficient and sustainable energy utilization through nanoscale design and control.
[0003] Among the known one-dimensional semiconductor nanomaterials, zinc oxide (Zinc Oxide) nanomaterials have become popular functional materials for the following reasons. First, it has a large specific surface area, good crystal quality, and unique photonic properties; second, ZnO can use a variety of techniques to synthesize idealized microscopic morphologies, such as nanowires, nanorods, etc.; finally, the preparation cost of ZnO is low, and it can be synthesized on various substrates, which is suitable for more application scenarios. There are many ways to synthesize ZnO, such as MOCVD, thermal evaporation, hydrothermal growth, electrochemical thermal deposition, etc., which can synthesize ZnO nanostructures on different substrates, such as nanowires, nanorods, nanoflowers, etc. However, in some application areas, the energy conversion efficiency of ZnO is still limited. For example, in the field of light-to-electricity conversion, both photovoltaic and photoconductive photodetectors have problems such as low photoelectric conversion efficiency; in addition, the photoelectric conversion efficiency of solar cells prepared using 20μm ZnO nanowires is only 1.5%. In order to solve such problems, the specific surface area of the ZnO nanostructure can be increased to achieve the contact area between light and matter, thereby improving the conversion efficiency.
[0004] At present, compared with the randomly arranged ZnO nanorod structure, the periodic ZnO nanoarray structure has more advantages, such as uniform separation, high symmetry and adjustability. In addition, the separated nanoarray structure can significantly increase the surface area of ZnO, making it have higher activity and efficiency in the fields of catalysis and photoelectric conversion. The periodic structure has better mechanical stability and compressive resistance, which is suitable for application in complex environments. The periodic layout of the nanoarray structure makes the preparation process relatively controllable and repeatable, which is conducive to large-scale production and industrial application.
[0005] Therefore, there is an urgent need for a ZnO nanoarray structure that is simple to prepare, can be produced on a large scale, and has a simple and controllable size. Summary of the invention
[0006] The present invention provides a size-adjustable zinc oxide nanoarray and a preparation method and application thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.
[0007] In order to achieve the above-mentioned object, the embodiment of the present invention provides a size-adjustable zinc oxide nanoarray and its preparation method and application, and realizes the size-controllable ZnO nanoarray structure by changing the photolithography template. Using a specific photolithography template, the discrete ZnO nanoarrays are kept at a suitable distance, and the morphology is consistent to meet the needs of specific application scenarios. The present invention prepares a ZnO nanorod array cluster structure by entering the photolithography template during the hydrothermal growth process. The structure has the advantages of good uniformity, excellent enhancement effect, simple preparation method, low cost, and repeatability.
[0008] An embodiment of the present invention provides a size-adjustable zinc oxide nanoarray, comprising a conductive film and a zinc oxide nanorod array cluster;
[0009] Among them, zinc oxide nanorods grow upright on the conductive film, and the zinc oxide nanorods grow in clusters to form array clusters; the array cluster structure shows large-area periodic growth and periodic distribution on the conductive film.
[0010] According to one aspect of the embodiments of the present invention, the conductive film is indium tin oxide and has a thickness of 65 nm.
[0011] According to one aspect of the embodiments of the present invention, the zinc oxide nanorod array cluster is a cluster array formed by a plurality of upright zinc oxide nanorods; the top view shape of a single zinc oxide nanorod array cluster is determined by a template, and the size of the template can be adjusted to micron precision.
[0012] According to one aspect of the embodiments of the present invention, the zinc oxide nanorods have a shape of upright hexagonal prisms with a diameter of 200-300 nm and a height of 1.2 μm.
[0013] Based on a general concept of the invention, an embodiment of the present invention provides a method for preparing a size-adjustable zinc oxide nanoarray, comprising the following steps:
[0014] S1: pre-treating a glass substrate with an ITO film; preparing a zinc oxide seed layer solution;
[0015] S2: Spin-coating a zinc oxide seed layer solution on a pre-treated glass substrate having an ITO film, and placing the solution in a box furnace for annealing and orientation after curing to obtain a zinc oxide seed layer;
[0016] S3: Spin-coating a photoresist on the seed layer, exposing it to light and soaking it in a developing solution to obtain a zinc oxide seed layer with a hole template;
[0017] S4: Place the zinc oxide seed layer with the hole template obliquely against the side wall of the reactor inner tank, facing downward, add a hydrothermal solution of zinc nitrate and hexamethylenetetramine, obtain zinc oxide nanorod array clusters through hydrothermal reaction, and then remove the photoresist.
[0018] According to one aspect of an embodiment of the present invention, in step S1, the pretreatment process includes ultrasonic cleaning with acetone and alcohol, and high-temperature drying; the seed layer solution preparation process is: using anhydrous ethanol as a solvent, preparing 0.3 mol / L zinc acetate dihydrate, and then adding 0.3 mol / L ethanolamine, sealing, heating to 40°C and magnetically stirring until completely dissolved, and standing at room temperature for 24 hours.
[0019] According to one aspect of the embodiment of the present invention, in step S2, the single spin coating speed is 4000 rpm, the time is 20 s; the spin coating is performed 12 times; the curing temperature is 80° C., the time is 10 min; and the annealing temperature is 500° C., the time is 30 min.
[0020] According to one aspect of the embodiments of the present invention, in step S3, after spin coating the photoresist, the photoresist is baked at 100° C. for 1 minute, and immersed in a developer for 65 seconds.
[0021] According to one aspect of an embodiment of the present invention, in step S4, the hydrothermal solution preparation process is: using deionized water as a solvent, taking 0.003 mol / L polyethyleneimine, 0.05 mol / L zinc nitrate hexahydrate and 0.05 mol / L hexamethylenetetramine to mix, sealing, heating to 40°C and magnetically stirring for 1 hour, to obtain; the hydrothermal temperature is 90°C and the time is 2 hours; after the hydrothermal reaction, it is washed and dried with deionized water; the process of removing the photoresist is: soaking in acetone for 30 seconds, and then soaking in anhydrous ethanol and deionized water for 1 minute each.
[0022] Note: The time for removing ZnO by acetone immersion should not be too long, preferably no more than 30 seconds. ZnO and acetone do not react directly, but acetone molecules are adsorbed on the ZnO surface. The adsorbed acetone molecules will react with oxygen species on the ZnO surface (such as O - 、O2 - These oxygen species are formed by the ionization of oxygen molecules adsorbed by ZnO in the air. Acetone molecules react with these oxygen species, resulting in the redistribution of electrons on the ZnO surface. These reactions may include partial oxidation of acetone molecules, the generation of some small molecules (such as CO2 and H2O) and the release of electrons. This type of surface adsorption and charge transfer process will affect the physical and chemical properties of ZnO itself, which is not conducive to subsequent applications.
[0023] The embodiments of the present invention also provide the application of the above-mentioned size-adjustable zinc oxide nanoarray or the size-adjustable zinc oxide nanoarray obtained by the above-mentioned preparation method in the field of light-to-electricity conversion.
[0024] According to one aspect of an embodiment of the present invention, it is specifically applied to different fields such as photodetectors, photocatalysts, solar cells, etc.
[0025] The above scheme of the present invention has the following beneficial effects:
[0026] (1) The present invention can precisely control the morphology and size of the template, thereby achieving precise positioning and control of the growth of the ZnO nanorod array cluster, which is conducive to the formation of a uniformly arranged nanostructure. Compared with the ZnO nanorods in the prior art, the present invention achieves templated regular regional growth instead of large-area messy upright ZnO nanorod growth.
[0027] (2) The preparation method of the present invention is simple and efficient, and can realize large-area template preparation, thereby realizing large-area array growth. At the same time, the photolithography template is relatively stable, does not interact with the hydrothermal reaction, and has a high synthesis efficiency; different templates can also be designed according to the corresponding application scenarios to achieve different array shapes and array spacings, thereby obtaining better morphology control, which is a control method with a high success rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 It is a schematic flow chart of a method for preparing a size-adjustable zinc oxide nanoarray of the present invention;
[0030] Figure 2 It is a schematic structural diagram of a size-adjustable zinc oxide nanoarray of the present invention;
[0031] Figure 3 This is a real-life picture of a hole template of a size-adjustable zinc oxide nanoarray of the present invention;
[0032] Figure 4 This is a 5μm optical microscope image of a hole template of a zinc oxide nanoarray with adjustable size according to the present invention;
[0033] Figure 5 This is a 10 μm optical microscope image of a hole template of a zinc oxide nanoarray with adjustable size according to the present invention;
[0034] Figure 6 It is an optical microscope image of zinc oxide nanorod array clusters of different sizes of the present invention, and the side lengths of the arrays from left to right correspond to 3, 4, and 5 μm, respectively. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0038] The energy conversion efficiency of ZnO is still limited. For example, in the field of light-to-electricity conversion, both photovoltaic and photoconductive photodetectors have problems such as low photoelectric conversion efficiency. In addition, the photoelectric conversion efficiency of solar cells prepared using 20μm ZnO nanowires is only 1.5%.
[0039] The embodiment of the present invention provides a size-adjustable zinc oxide nanoarray, the structure of which is as follows: Figure 2 As shown, the ZnO nanoarray structure includes: a conductive film, a ZnO nanorod array cluster; the ZnO nanorods grow upright on the conductive film glass, and some ZnO nanorods grow together to form an array cluster, and the array cluster structure shows large-area periodic growth on the conductive film glass.
[0040] In some embodiments of the present application, the ZnO nanoarray structure implemented by the photolithography template is, from top to bottom, ZnO nanorods and conductive film glass.
[0041] In some embodiments of the present application, the thin film on the conductive thin film glass is indium tin oxide (ITO).
[0042] In some embodiments of the present application, the thickness of the conductive film is 65 nm. The glass substrate is 1 cm×1 cm and has a thickness of 1100·μm.
[0043] In some embodiments of the present application, the ZnO nanorod array cluster is a cluster array formed by a plurality of upright growing nanorods.
[0044] In some embodiments of the present application, the top-view shape of the single nanorod array is determined by a template, and the size is adjustable with an accuracy of microns.
[0045] In some embodiments of the present application, the morphology of a single nanorod in the array is a right hexagonal prism with a diameter of about 200-300 nm and a height of about 1.2 μm.
[0046] Figure 4 Corresponding to a single array being a square with a side length of 5 μm, the specific size adjustment can be changed according to the size and shape of the template.
[0047] In some embodiments of the present application, the materials required for preparing the ZnO nanoarray structure realized by the above-mentioned photolithography template are: (1) 1 cm×1 cm glass sheet with ITO film; (2) acetone solution, anhydrous ethanol, deionized water; (4) zinc acetate dihydrate powder, zinc nitrate hexahydrate powder, ethanolamine solution, polyethyleneimine solution, hexamethylenetetramine powder; (5) AZ6112 photoresist, developer.
[0048] The embodiment of the present invention provides a method for preparing the above-mentioned size-adjustable ZnO nanoarray structure, the flow chart of which is as follows: Figure 1 As shown, the following steps are included:
[0049] Step 1. First, a 1×1 cm glass with indium tin oxide (ITO) was ultrasonically cleaned in acetone, ethanol, and deionized water for 10 min in sequence, blown dry, and set aside for use.
[0050] Step 2. The steps for preparing the seed layer solution are as follows: 30 mL of ethanol is used as the solvent, 0.3 mol / L of zinc acetate dihydrate is added, and then 0.3 mol / L of ethanolamine is added as the complexing agent. The solution is magnetically stirred at 40°C for 10 minutes until it is completely dissolved. The seed layer solution is allowed to stand for 24 hours to solidify.
[0051] Step 3. Use a pipette to draw 50 μL of seed layer solution and drop it onto the ITO glass. Use a coater to coat the entire glass. The speed of the coater is 4000 r / min, and the single coat lasts for 20 seconds. Repeat the above steps 12 times. Place the ITO glass with the seed layer on a hot plate and bake at 80°C for 10 minutes. In order to make the ZnO nanorods grow upright, place the sheet in a quartz ark, put it in a box furnace, and calcine it in an air atmosphere for 30 minutes to complete the preparation and orientation of the seed layer.
[0052] Step 4. Drop an appropriate amount of positive photoresist AZ 5124 on the seed layer and place it in a 3000r / min coating machine for 1 minute to make it uniform in thickness. Place the wafer on a 100℃ hot plate and bake for 1 minute to cure the photoresist. Expose the template pattern in the photolithography machine, then take it out and place it in the developer for 65 seconds to dissolve the denatured photoresist. Finally, put it in deionized water to wash the denatured photoresist to obtain the template on the seed layer.
[0053] Step 5. Perform hydrothermal growth on the seed layer with the template. First, prepare a hydrothermal solution, use 30 mL of deionized water as the solvent, and add 0.003 mol / L of polyethyleneimine, 0.05 mol / L of hexamethylenetetramine, and 0.05 mol / L of zinc acetate hexahydrate. Stir the hydrothermal solution magnetically at 40°C for 1 hour until it is completely dissolved. Place the wafer in step 3 diagonally downward on the side wall of the inner tank of the reactor, and then slowly pour in the hydrothermal solution. Place the reactor in a vacuum drying oven, and react at high temperature and high pressure at 90°C for about 2 hours for hydrothermal growth.
[0054] Step 6. Remove the grown wafer from the reactor liner and clean the surface residue with deionized water. Place the cleaned wafer in acetone for 30 seconds to remove the photoresist, and then place it in ethanol and deionized water to clean as much as possible. Let the wafer stand and air dry naturally.
[0055] In some embodiments of the present application, in step 3, the seed layer is spun at least 12 times to obtain a thicker and more uniform seed layer. In addition, the sintering and orientation are performed in a box furnace, and the target temperature cannot be less than 450° C. The temperature has a great influence on the lattice orientation.
[0056] In some embodiments of the present application, in step 4, the photoresist baking device is a hot stage, and the exposure intensity is adjusted accordingly according to the thickness of the photoresist.
[0057] In some embodiments of the present application, in step 5, the hydrothermal temperature error is controlled within 0.5°C, and the hydrothermal time error is controlled within 10 minutes.
[0058] In step 6, the time for removing ZnO by immersion in acetone should not be too long, not more than 30 seconds. ZnO and acetone do not react directly, but acetone molecules are adsorbed onto the ZnO surface. And the adsorbed acetone molecules will react with oxygen species (such as O - 、O2 - These oxygen species are formed by the ionization of oxygen molecules adsorbed by ZnO in the air. Acetone molecules react with these oxygen species, resulting in electron redistribution on the surface of ZnO. These reactions may include partial oxidation of acetone molecules, the generation of some small molecules (such as CO2 and H2O) and the release of electrons. This type of surface adsorption and charge transfer process will affect the physical and chemical properties of ZnO itself, which is not conducive to subsequent applications.
[0059] Example 1
[0060] Step 1: Clean the glass
[0061] Take a 1cm×1cm, 1100·μm thick ordinary quartz glass sheet, ultrasonically clean it in acetone solution, anhydrous ethanol and deionized water for 10 minutes, then blow it dry with a spray gun, and then place the glass sheet on a hot plate at 80℃ for 5 minutes. Finally, let the glass sheet cool naturally at room temperature to obtain a clean glass substrate.
[0062] Step 2: Prepare the seed layer
[0063] Use 30 mL of anhydrous ethanol as solvent, prepare 0.3 mol / L zinc acetate dihydrate, add 0.3 mol / L ethanolamine as complexing agent, seal with sealing film, heat to 40°C and stir magnetically until completely dissolved, and let stand at room temperature for 24 hours. The purpose is to obtain a seed layer solution with higher viscosity.
[0064] Step 3: Spin coating the seed layer
[0065] Place the cleaned and dried glass sheet in step 1 on the stage of the coating machine, use a pipette to absorb 50 μL of seed layer solution at a time, and evenly drip it on the glass sheet. Set the coating machine to a single speed of 4000 rpm for 20 seconds; repeat the above spin coating steps 12 times; place the spin-coated glass sheet on a hot plate and heat it at 80°C for 10 minutes; place the cured glass sheet in a box furnace and calcine it at 500°C for 30 minutes for lattice orientation. The oriented seed layer ensures the upright growth of the subsequent ZnO nanorods.
[0066] Step 4: Prepare the Mask
[0067] The glass slide with the seed layer prepared was placed in a coater, spin-coated with a layer of AZ 6112, and then pre-baked on a hot stage at 100°C for 1 min. After exposure in a photolithography machine, it was immersed in a developer for 65 seconds, and finally placed in deionized water to wash away the denatured photoresist, and dried naturally to obtain a seed layer with an array template.
[0068] Step 5: Hydrothermal growth of ZnO nanorods
[0069] Use 30mL of deionized water as solvent, mix 0.003mol / L polyethyleneimine, 0.05mol / L zinc nitrate hexahydrate and 0.05mol / L hexamethylenetetramine, seal with sealing film, heat at 40℃ and stir magnetically for 1h; place the glass piece obliquely downward against the side wall of the reactor, add the above-prepared solution, put it in an oven and react at 90℃ for 2h; after the hydrothermal reaction, take out the glass piece, put it in deionized water to wash away the precipitated impurities, and vacuum dry it at 60℃ for 1h.
[0070] Step 6: Removing the Photoresist
[0071] The glass substrate with the ZnO nanoarray obtained in the above steps was immersed in acetone for 30 seconds to remove the photoresist. During this period, the glass substrate was gently shaken with tweezers to fully remove the photoresist. Then, anhydrous ethanol and deionized water were immersed in each for 1 minute to remove the residual organic matter, and a relatively clean ZnO nanoarray structure on the glass substrate was obtained.
[0072] The implementation advantages of the present invention are:
[0073] (1) The present invention can precisely control the morphology and size of the template, thereby achieving precise positioning and control of the growth of the ZnO nanorod array cluster, which is conducive to the formation of a uniformly arranged nanostructure. Compared with the ZnO nanorods in the prior art, the present invention achieves templated regular regional growth instead of large-area messy upright ZnO nanorod growth.
[0074] (2) The preparation method of the present invention is simple and efficient, and can realize large-area template preparation, thereby realizing large-area array growth. At the same time, the photolithography template is relatively stable, does not interact with the hydrothermal reaction, and has a high synthesis efficiency; different templates can also be designed according to the corresponding application scenarios to achieve different array shapes and array spacings, thereby obtaining better morphology control, which is a control method with a high success rate.
[0075] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A size-adjustable zinc oxide nanoarray, characterized in that: including conductive films and zinc oxide nanorod array clusters; Among them, zinc oxide nanorods grow upright on the conductive film, and the zinc oxide nanorods grow in clusters to form array clusters; the array cluster structure shows large-area periodic growth and periodic distribution on the conductive film.
2. The size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: The conductive film is indium tin oxide and has a thickness of 65 nm.
3. The size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: The zinc oxide nanorod array cluster is a cluster array formed by a plurality of upright-growing zinc oxide nanorods; The top-view shape of a single ZnO nanorod array cluster is determined by the template, whose size can be adjusted to micrometer precision.
4. The size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: The zinc oxide nanorod has a shape of a vertical hexagonal prism with a diameter of 200-300 nm and a height of 1.2 μm.
5. A method for preparing a size-adjustable zinc oxide nanoarray, characterized in that: The steps include: S1: pre-treating a glass substrate with an ITO film; preparing a zinc oxide seed layer solution; S2: Spin-coating a zinc oxide seed layer solution on a pre-treated glass substrate having an ITO film, and placing the solution in a box furnace for annealing and orientation after curing to obtain a zinc oxide seed layer; S3: Spin-coating a photoresist on the seed layer, exposing it to light and soaking it in a developing solution to obtain a zinc oxide seed layer with a hole template; S4: Place the zinc oxide seed layer with the hole template obliquely against the side wall of the reactor inner tank, facing downward, add a hydrothermal solution of zinc nitrate and hexamethylenetetramine, obtain zinc oxide nanorod array clusters through hydrothermal reaction, and then remove the photoresist.
6. The method for preparing a size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: In step S1, the pretreatment process includes ultrasonic cleaning with acetone and alcohol, and high-temperature drying; the seed layer solution preparation process is: using anhydrous ethanol as a solvent, preparing 0.3 mol / L zinc acetate dihydrate, and then adding 0.3 mol / L ethanolamine, sealing, heating to 40°C and magnetically stirring until completely dissolved, and standing at room temperature for 24 hours.
7. The method for preparing a size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: In step S2, the single spin coating speed is 4000 rpm, the time is 20 s; the spin coating is performed 12 times; the curing temperature is 80° C., the time is 10 min; and the annealing temperature is 500° C., the time is 30 min.
8. The method for preparing a size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: In step S3, after spin coating the photoresist, the substrate is baked at 100° C. for 1 min, and immersed in a developer for 65 s.
9. The method for preparing a size-adjustable zinc oxide nanoarray according to claim 1, characterized in that: In step S4, the hydrothermal solution preparation process is: using deionized water as a solvent, taking 0.003 mol / L polyethyleneimine, 0.05 mol / L zinc nitrate hexahydrate and 0.05 mol / L hexamethylenetetramine to mix, sealing, heating to 40°C and magnetically stirring for 1 hour, the hydrothermal temperature is 90°C, and the time is 2 hours; after the hydrothermal reaction, it is washed and dried with deionized water; the process of removing the photoresist is: soaking in acetone for 30 seconds, and then soaking in anhydrous ethanol and deionized water for 1 minute each.
10. Use of a size-adjustable zinc oxide nanoarray according to any one of claims 1 to 4 or a size-adjustable zinc oxide nanoarray obtained by the preparation method according to any one of claims 5 to 9 in the field of photo-electric conversion.
